Pemberdayaan Pasangan Usia Subur untuk Berperan Serta Aktif dalam Peningkatan Penggunaan Alat Kontrasepsi - Friza N. S Situmorang; Anna Waris Nainggolan; Edy Marjuang Purba; Yasrida Nadeak; Rasmi Manullang; Oni Kurnia; Yemima Siadari (TAAWUN, 2023)
The Central Statistics Agency (BPS) stated that the total population in North Sumatra reached 14,242. 678 thousand people and the population growth rate is still above 1.5 percent per year. The results of interviews with Hamidah PMB officers stated that the active role of husband and wife in the use of contraceptives was still quite low so that the impact on awareness of the use of contraceptives was quite low. The purpose of this community service activity is to increase the active role of husband and wife in using contraceptives in the BPM Hamidah area, Medan Maimun District, so that it can help realize the government's program to reduce the number of population births, as well as control the population in general for the creation of a healthy community welfare. and prosperous. The method of implementing the activity is carried out by conducting counseling to married couples regarding the importance of using contraception and planning pregnancy. Based on the results of the empowerment carried out, it was found that there was an increase in the husband's knowledge about the use of contraceptives. Prior to counseling, they had less knowledge (47.8%), but after counseling, most of them had good knowledge (69.6%). In addition, there was also an increase in the knowledge of the wives, where before counseling was carried out, more and more were knowledgeable enough and lacking, respectively (34.8%), but after counseling was carried out most of them had good knowledge (86.9%). It was expected that BPM Hamidah would conduct counseling regarding contraception and assistance to married couples on an ongoing basis